Analisis Pengukuran Tingkat Kepuasan Dosen Terhadap Sistem Informasi Akademik Menggunakan Metode Usability Pada Universitas Prabumulih - Resky Klarasati; Tata Sutabri (Fakultas Teknologi dan Ilmu Komputer Universitas Prima Indonesia, 2023)
The rapid development of technology has led to a new civilization, institutions, and companies competing to improve services by utilizing information technology. The use of technology, one of which is useful for services in high schools and tertiary institutions, both public and private, in this case, the Academic Information System (SIAKAD) system, has been implemented at Prabumulih University. However, this system has only been implemented by the campus, so some lecturers still need to understand the use of SIAKAD. From the description above, the researcher is interested in analyzing the level of lecturer satisfaction in implementing the SIAKAD system so that the first aim is to improve complete academic services (plenary) to students. The second can schedule guidance to students through the lecturer account in the SIAKAD system, and the third can see class schedules and can schedule E-Learning lectures in the SIAKAD system to be presented accurately in digital terms, so to achieve this goal researchers use quantitative data with the Usability method, data collection techniques for distributing questionnaires virtually via WhatsApp grub where the questionnaire has been created using the google form, then the completed questionnaire was processed using IBM's SPSS in order to obtain a level of satisfaction in the usability of the SIAKAD system. The statement above as a result of the conclusions of this study, it is hoped that the SIAKAD system can be used optimally by Prabumulih University.